PENGARUH MOTIVASI MEMASUKI DUNIA KERJA DAN PENGALAMAN PRAKTIK KERJA INDUSTRI (PRAKERIN) TERHADAP KESIAPAN KERJA SISWA KELAS XII SMK NEGERI 5 KUNINGAN - Rizki Ananda Putri; Cucu Suhartini (Universitas Kuningan, 2021)
The research was purposed for describing : 1) The student perceptions about motivations to join with the corporate world, Field Industrial Practice experienced and study working readiness. 2) the influences of motivations to student working readiness. 3) the influences of Field industrial practice experience to student working readiness. 4) the influences of motivations to the corporate world and Field industrial practice experience to student working readiness of Twelfth grade in SMKN 5 Kuningan.This research using kuantitatif methods. Populations in this research is the students in the twelfth grade in SMKN 5 kuningan as 236 students. Technique to finds sample using Probability Sampling with the sampling result as 148 students. For data collections technique using by researcher is questionnaire.Based on the result of processing and analisys, the result obtained for an value of 1156,3. Calculated F Value (1156,3) F on the tabel (3,06) with the calculated Sig.5% it means the motivations to entered the workforce and Field industrial practice experience have a positive influence to student working readiness.Based on the result of the research that has been done then : 1) School or teacher can improving student working readiness with giving an support and pushing motivations through work guidance, motivational seminars and expertise workshops, 2) for increase working readiness, the school can provide encouragement and monitoring the development of students abilities during Field industrial practices as well as providing learning facilities that are appropriate to those in DU / DI so that they can support student skills, 3) The school is more paying attention for Field industrial practice place accordance with students expertise with giving instructions to choose Field industrial practice places especially for school that have policy to submit the place of Field industrial practicing for students.Keywords : Motivation Entering The World Of Work, Field Industrial Practice Experiences , Student Working Readiness.